Postpartum Massage and Traditional Herbs on Accelerating Uterine Involution in Postpartum Mothers - Arsulfa Arsulfa; Heyrani Heyrani; Sitti Aisa; Hesti Resyana; Malahayati Malahayati (Journal of Liaquat University of Medical & Health Sciences, 2025)
Objective: To analyze the effect of postpartum massage and traditional herbs on the acceleration of uterine involution in postpartum mothers Methodology: A purposive sampling technique was used to select participants from among postpartum mothers who visited the health center. This study included 120 postpartum mothers aged 18-35 who had given birth normally. Participants were excluded due to potential complications during labour. The study, conducted at the Puuwatu Health Centre in Kendari, Indonesia, employed a quasi-experimental design with a pretest-posttest control group approach involving postpartum mothers. Data collection tools included questionnaires for demographic assessment, as well as experiences with postpartum massage and herbal treatment, and tapes for the direct measurement of UFH at baseline and post-intervention intervals. Data were collected at four postpartum intervals, and the results were analyzed using the Kruskal-Wallis and Mann–Whitney tests. Results: There was a significant difference in the acceleration of uterine involution between Groups 1 and 2 and the control group (p = 0.001). The comparison between intervention group 1 and the control group yielded a p-value of 0.000, indicating a statistically significant difference in the acceleration of uterine involution, with intervention group 1 showing the most favourable results. The comparison between intervention group 2 and the control group yielded a p-value of 0.001, indicating a statistically significant difference, with intervention group 2 showing better results than the control group. Conclusion: Postpartum massage intervention and the use of traditional herbs had a significant positive effect on the acceleration of uterine involution in postpartum mothers.